Evaluation of nursing students' engagement in two different simulation modalities - Burcu Dogan (18505001) (2024)
Background Simulation-based education has been increasingly integrated into healthcare professional training owing to its proven efficacy in enhancing clinical skills and knowledge within a secure and supervised setting. While Full-Scale Simulation (FSS) has established itself as a prevalent method in healthcare education, Visually Enhanced Mental Simulation (VEMS) stands as an emerging and innovative simulation modality. VEMS incorporates visual representations of patients and equipment, encourages students to articulate their thought processes through think-aloud techniques, and fosters engagement with clinical scenarios, mirroring the immersive experiences offered by FSS while practising non-technical skills (1,2). In this study, our objective is to compare the evaluation of nursing students regarding FSS and VEMS sessions that they attended. Methods This mixed-methods study involved 150 nursing students, of which 103 third-year students willingly assessed the simulation sessions they attended using the Simulation Effectiveness Tool-Modified (SET-M) (3). These students were divided into two groups: 65 students participated in and assessed Full-Scale Simulation (FSS), while 38 students evaluated Visually Enhanced Mental Simulation (VEMS) sessions. Both groups were exposed to identical scenarios, and the sessions were conducted using similar instructional techniques. Results In comparing students' SET-M scores for the two different simulation modalities, VEMS received a higher ranking than FSS (p=0.03). Notably, since the simulation sessions shared comparable instructional methods, there was no significant difference in how students rated the pre-briefing and debriefing sessions (p=0.23 and p=0.46, respectively). However, subscales related to learning and confidence, which pertained to the scenario itself, exhibited statistically significant differences (p=0.007 and p=0.03, respectively). Specifically, students consistently ranked VEMS higher than FSS (Table 1). Conclusion This study suggests that VEMS can deliver a level of engagement similar to that of FSS. Therefore, VEMS holds promise as an alternative to FSS, particularly when focusing on the development of non-technical skills.